Proposição de ferramenta de gerenciamento de resíduos da construção civil para canteiros de obras de galpões industriais - Gomes, Pedro Luiz Ferreira (2024)
Human development has intensively exploited natural resources over time, and sustainability aims to transform this pattern to ensure responsible resource use and preserve them for future generations. In the construction sector, waste management (C&D waste) is a significant challenge, especially with the requirements of the National Solid Waste Policy (PNRS), which mandates municipalities to create C&D Waste Management Plans and oversee waste generators. Compared to international practices, Brazil still faces challenges, such as the lack of pre-demolition audits and waste traceability—critical aspects in industrial warehouse projects, which lack sustainable management models. In response to this scenario, this dissertation proposed a C&D waste management tool for industrial warehouse construction sites, based on extensive bibliographic and documentary research. Legislation, standards, and resolutions, both national and international, were reviewed, along with academic articles and environmental certifications focused on C&D waste management. To consolidate the information, a comparative matrix was used, in which 699 records were entered. Of these, 183 were considered highly relevant for the tool’s development. The results highlight practices such as the use of modern construction methods and efficient supply chain planning for inventory control and the promotion of resilient secondary materials markets. Comparative analysis of standards, resolutions, and certifications revealed discrepancies in waste management between Brazil and international practices. Based on this, 111 micro C&D waste management indicators were proposed for construction sites, and 64 macro-level improvement opportunities were identified to guide future studies. Going forward, the tool is intended to be applied across different construction sites to gather feedback from field teams, thus refining the proposed indicators and contributing to sustainable construction waste management in industrial projects.